Hubungan Kecenderungan Perilaku Narsistik dengan Penerimaan Diri Remaja Pengguna Media Sosial Instagram di SMAN 2 Kota Tasikmalaya - Ayu Fitriani Solihah; Eva Rahayu; Wahyu Ekowati (Journal of Bionursing, 2023)
Background. : Narcissistic behavioral tendencies are self-loving behaviors and have a need to be adored or appreciated. The tendency of this narcissistic behavior can unwittingly affect the self-acceptance of a teenager. This study aims to determine the relationship between narcissistic behavior tendencies and self-acceptance in adolescents who use Instagram social media. Methods. The design of this research is correlational analysis and quantitative research approach cross sectional. Sampling using purposive sampling with research respondents totaling 93 respondents. The research instrument is a questionnaire that uses a Likert scale and uses an ordinal measuring scale. Bivariate analysis using Somers'd test. Results. The results of the univariate characteristics of the respondents obtained a median of 17 years and the majority were female as much as 63.4%. The majority of respondents had a tendency to narcissistic behavior in the less narcissistic category of 52.7% and high self-acceptance of 53.8%. The results of the correlation hypothesis obtained a p-value of 0.000 (P<0.05) and r=0.936. Conclusion. There is a negative relationship between narcissistic behavior tendencies and self-acceptance of social media users instagram with very strong power. The higher the tendency of narcissistic behavior, the lower the self-acceptance of adolescents who use social media instagram.